Gnotobiotic Rodents: An In Vivo Model for the Study of Microbe–Microbe Interactions - Martín, Rebeca; Bermúdez-Humarán, Luis G.; Langella, Philippe (Frontiers in Microbiology, 2016)
Germ-free rodents have no microorganisms living in or on them, allowing researchers to specifically control an animal’s microbiota through the direct inoculation of bacteria of interest. This strategy has been widely used to decipher host-microbe interactions as well as the role of microorganisms in both i) the development and function of the gut barrier (mainly the intestinal epithelium) and ii) homeostasis and its effects on human health and disease. However, this in vivo model also offers a more realistic environment than an assay tube in which to study microbe-microbe interactions, without most of the confounding interactions present in the intestinal microbiota of conventionally raised mice. This review highlights the usefulness of controlled-microbiota mice in studying microbe-microbe interactions. To this end, we summarize current knowledge on germ-free animals as an experimental model for the study of the ecology and metabolism of intestinal bacteria as well as of microbe-microbe interactions.